The Effect of Destination Image and Social Influence on Visiting Intentions and Visiting Decisions at Museum - Noviana, Nengah Mekka Sucia; Achmad, Gusti Noorlitaria; Wahyuni, Sri (Green Publisher Indonesia, 2022)
The purpose of this study was to analyze and prove the effect of destination image and social influence on visiting intentions and visiting decisions on visitors to the Mulawarman museum in Kutai Kartanegara Regency. This study used 120 respondents and this study used a survey method with a sample in Kutai Kartanegara Regency with the Accidental Sampling Method sampling technique. Respondents were only interviewed once when they met (cross section). Data from respondents (Primary Data) was then tabulated and tested using statistical methods. Data were collected using research tools (questionnaires). Based on the results of the analysis and discussion, it can be concluded that the image of the destination has a significant effect on the visiting intentions of visitors. So the better the image of the destination, the higher the intention to visit. Social has no significant effect on visitors' intention to visit. So the better the social level, the higher the intention to visit. The image of the destination has no significant effect on the decision to visit the visitors. So the high or low level of the image of the destination does not affect the decision to visit. Social influence has a significant effect on the decision to visit. So the better the social level, the higher the decision to visit. Intention to visit has a significant effect on the decision to visit. So the higher the intention to visit, the higher the decision to visit.